Immune checkpoint inhibition in patients with NRAS mutated and NRAS wild type melanoma: a multicenter Dermatologic Cooperative Oncology Group study on 637 patients from the prospective skin cancer registry ADOREG - Zaremba, Anne; Mohr, Peter; Gutzmer, Ralf; Meier, Friedegund; Pföhler, Claudia; Weichenthal, Michael; Terheyden, Patrick; Forschner, Andrea; Leiter, Ulrike; Ulrich, Jens; Utikal, Jochen; Welzel, Julia; et al. (European Journal of Cancer, 2023)
Background: Melanomas frequently harbour somatic mutations in BRAF (40%) or NRAS (20%). Impact of NRAS mutations on the therapeutic outcome of immune checkpoint inhibitors (ICI) remains controversial. Potential correlation of the NRAS mutational status and programmed cell death ligand-1 (PD-L1) expression in melanoma is unknown. Patients and methods: Advanced, non-resectable melanoma patients with known NRAS mutation status treated with first-line ICI between 06/2014 and 05/2020 in the prospective multicenter skin cancer registry ADOREG were included. Overall response rate (ORR), progression-free survival (PFS), and overall survival (OS) according to NRAS status were analysed. A multivariate Cox model was used to analyse factors associated with PFS and OS; survival was analysed using the Kaplan–Meier approach. Results: Among 637 BRAF wild-type patients, 310 (49%) had an NRAS mutation with Q61R (41%) and Q61K (32%). NRAS-mutated (NRASmut) melanomas were significantly more often located on the lower extremities and trunk (p = 0.001); nodular melanoma was the most common subtype (p < 0.0001). No significant differences were found for PFS and OS for anti-PD1 monotherapy (2-year PFS 39%, [95% confidence interval (CI), 33–47] in NRASmut patients and 41% [95% CI, 35–48] in NRAS-wild type (NRASwt) patients; 2-year OS was 54% [95% CI, 48–61] in NRASmut patients and 57% [95% CI, 50–64] in NRASwt patients) and anti-PD1 plus anti-CTLA4 therapy between both cohorts (2-year PFS was 54% [95% CI, 44–66] in NRASmut patients and 53% [95% CI, 41–67] in NRASwt patients; 2-year OS was 58% [95% CI, 49–70] in NRASmut patients and 62% [95% CI, 51–75] in NRASwt patients). The ORR to anti-PD1 was 35% for NRASwt patients and 26% for NRASmut patients and 34% compared to 32% for combinational therapy. Data on PD-L1 expression was available in 82 patients (13%). PD-L1 expression (> 5%) was not correlated to NRAS mutational status. In multivariate analysis, elevated lactate dehydrogenase, Eastern Cooperative Oncology Group performance status ≥ 1, and brain metastases were significantly associated with a higher risk of death in all patients. Conclusions: The PFS and OS were not affected by NRAS mutational status in patients treated with anti-PD1-based ICI. Similar ORR was seen in NRASwt and NRASmut patients. Tumour PD-L1 expression did not correlate with NRAS mutational status.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Immune checkpoint inhibitors; Immunotherapy; Melanoma